Nutritional status of 0-5 years children and its determinant in Maharashtra India - Wagh, Sanjay V.; Waghmare, Rakesh B.; Nehate, Harshal K.; Puri, Mahesh (International Journal Of Community Medicine And Public Health, 2019)
Background: Malnutrition is silent emergency and it is one of the most common causes of morbidity and mortality among children in India. India is home for underweight children. Hence the present study attempt to assess the underweight status of 0-5 years children and to find out socio-demographic determinant with it in rural community of Maharashtra. Methods: A cross sectional study was conducted among 281 children aged 0-5 years. The study was conducted rural health training centre, Barshi Takali district Akola which is field practicing area of Community Medicine Department of Government Medical College, Akola. The data was analyzed using Epi-info-6. Results: 24.9% children were in the age group of 24-35 months. 33.8% fathers were educated up to high secondary 21%. Under five children were underweight. The proportion of under-five children with under-weight showed significant association with education of father, breast feeding and diarrhoea. Conclusions: Father education, breast feeding practices and diarrhoea were the important determinant for underweight that were found in the study. The information education and communication (IEC) is needed to for preventing the occurrence of under-nutrition among 0-5 years children.